2019
DOI: 10.1016/j.molmet.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The translational regulator FMRP controls lipid and glucose metabolism in mice and humans

Abstract: Objectives The Fragile X Mental Retardation Protein (FMRP) is a widely expressed RNA-binding protein involved in translation regulation. Since the absence of FMRP leads to Fragile X Syndrome (FXS) and autism, FMRP has been extensively studied in brain. The functions of FMRP in peripheral organs and on metabolic homeostasis remain elusive; therefore, we sought to investigate the systemic consequences of its absence. Methods Using metabolomics, in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 63 publications
(91 reference statements)
4
35
1
Order By: Relevance
“…Prior studies have focused on metabolic markers and have highlighted reduced levels of cholesterol [11][12][13] and abnormal abundances of the metabolic hormones leptin and adiponectin [14]. In a translational study addressing metabolic consequences of FMR1-deficiency both in a FXS mouse model and in FXS patients, we have recently shown that FXS patients display reductions in circulating glucose and increases in both free fatty acids and insulin, underlining metabolic anomalies in FXS [15]. Regarding possible immune dysfunctions in FXS, only a few studies have characterized FXS patients for immune biomarkers such as cytokines.…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…Prior studies have focused on metabolic markers and have highlighted reduced levels of cholesterol [11][12][13] and abnormal abundances of the metabolic hormones leptin and adiponectin [14]. In a translational study addressing metabolic consequences of FMR1-deficiency both in a FXS mouse model and in FXS patients, we have recently shown that FXS patients display reductions in circulating glucose and increases in both free fatty acids and insulin, underlining metabolic anomalies in FXS [15]. Regarding possible immune dysfunctions in FXS, only a few studies have characterized FXS patients for immune biomarkers such as cytokines.…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…It is both protein and mRNA null. This model has been widely used for drug testing (Deacon et al, 2015; Cheng et al, 2017; Gaudissard et al, 2017; Dahlhaus, 2018; Leboucher et al, 2019; Tranfaglia et al, 2019), and the battery of behavioral testing has been largely focused on hyperactivity, increased sensitivity to auditory stimuli, stereotypy and deficits in learning and memory (Olmos-Serrano et al, 2011). At the cellular and circuit levels, studies of the FXS mice have focused largely on overactive metabotropic glutamate receptor 5 (mGluR5) signaling (Dölen et al, 2007), increased protein synthesis (Osterweil et al, 2010), and enhanced long-term potentiation (LTP; Auerbach and Bear, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Murine Fmr1 -knock-out (KO) models of FXS have been generated, exhibiting CNS-related behavioral, and neuronal anomalies reminiscent of the human phenotypes (6, 7). The FMR1 gene is not only expressed in the central nervous system (CNS) but also in a variety of peripheral tissues, including adipose tissue, and liver (811). Adult skeletal and cardiac muscle are the only peripheral tissues tested so far not expressing FMRP, while both white adipose tissue (WAT) and brown adipose tissue (BAT) express FMRP (812).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that long-term pathological consequences of FMR1 -deficiency are not solely confined to the central nervous system disorders and more likely extend to physiological dysfunctions in peripheral systems. We have previously demonstrated in FXS mouse model how Fmr1- deficiency increased systemic utilization of lipids, reduced adiposity and provoked significant changes in metabolic homeostasis, some of which were also translatable to FXS patients (11). Besides presenting metabolic phenotypes, FXS is also accompanied by physical abnormalities (13).…”
Section: Introductionmentioning
confidence: 99%